Let's Talk About Mental Health and Mental Disorders in Elite Sports: A Narrative Review of Theoretical Perspectives - Lundqvist, Carolina; Andersson, Gerhard (Frontiers in Psychology, 2021)
The objective of this article is to discuss: (a) the various theoretical perspectives on mental health and mental health disorders adopted in sport psychology, and (b) how the adoption of these various theoretical perspectives in studies might impact upon the interpretations and conclusions in research about the mental health of participants in elite sports. Well-being as a target construct, holistic models, Keyes’ dual-continuum model, the single continuum, and stage models of mental health are described, together with a sports psychiatric view of mental health. The strengths and limitations of various mental health perspectives are discussed. We conclude that mental health is a complex construct and that the sport psychology literature, much like the clinical psychology literature, has struggled to reach a consensus regarding a definition or a feasible approach to investigating mental health. For the researcher, it becomes important to make explicit the underlying theoretical perspective adopted and the operationalization upon which conclusions about elite athletes’ mental health are based so that an increased knowledge base with high scientific credibility can be established and consolidated over time.